The role of NK cells in rheumatoid arthritis - Fathollahi, Anwar; Samimi, Leila Nejatbakhsh; Akhlaghi, Maassoumeh; Jamshidi, Ahmadreza; Mahmoudi, Mahdi; Farhadi, Elham (Inflammation research, 2021)
Objective Natural killer (NK) cells are part of the innate immune system which not only provides a primary response to pathogenic conditions but can also play an important regulatory role in immune responses. Furthermore, these cells can influence immune responses by affecting other involved cells. Human NK cells can be classified as CD56 dim and CD56 bright ; the former demonstrates mostly cytotoxic effects, while the latter comprises mostly tolerant or regulatory NK cells. These cells participate in the immunopathogenesis of rheumatoid arthritis (RA) and their role remains still unclear. Methods We searched PubMed/MEDLINE and Scopus databases to review and analyze relevant literature on the impact of NK cells in the pathogenesis of RA. Results Although the percentage of NK cells increases in peripheral blood of RA patients compared to healthy individuals, the cytotoxic function of these cells is impaired. It is demonstrated by reduced “perforin + NK cells” and decreased per-cell lytic function. These cytotoxic NK cells may control the pathogenic bone absorptive function of osteoclasts by directly targeting these cells. Conclusion Collectively, the evidence collected in the current review emphasizes the possible protective role of CD56 dim NK cells in the pathogenesis of RA.